AB0646 Intra-articular level of c-reactive protein in diagnosis of prosthetic knee infection. (23rd January 2014) - Ronde-Oustau, C.; Antoni, M.; Gaudias, J.; Boeri, C.; Sibilia, J.; Jenny, J.-Y.
Abstract : Background: Periprosthetic joint infection is a rare but potentially serious complication. In 2012, Parvizi et al. suggested intra-articular C-reactive protein (CRP) could be used as a diagnosis marker of periprosthetic joint infection, with a threshold of 9.5mg/L 1 . Objectives: The aim of our study was to analyse variations of CRP in synovial fluid between patients with native or prosthetic knee and find a threshold predictive of prosthetic knee infection. Methods: From February to August 2012, 31 patients were included in our study: 10 patients with effusion in their native joint, 11 with aseptic effusion on prosthetic knee, 10 patients with a prosthetic knee infection according to the 2011 Muskuloskeletal Society criteria. All cases underwent joint aspiration. Intra-articular CRP level was determined by nephelometry and compared to seric CRP. Results: Intra-articular CRP level was increased in patients with prosthetic knee infection compared to patients without prosthesis or aseptic prosthesis (respectively 24.4mg/L, 1.91 mg/L, 3.69mg/L; p=0.012, p<0.001). We used ROC curves using intra-articular CRP level from both prosthetic groups. A threshold of 2.78 mg/L might define a possible infection (sensibility 100%, specificity 81.82%), a threshold of 5.37 mg/L might define a probable infection (sensibility 90%, specificity 90.91%). Area under curve were not different for intra-articular CRP level (0.90) and seric CRP level (0.98). Conclusions: Our study showed that intra-articular CRP level could be a useful marker of prosthetic knee infection. The exact usefulness of this marker for the diagnosis of periprosthetic joint infection needs to be more precisely evaluated on a larger cohort. References: Parvizi J, McKenzie JC, Cashman JP. J Arthroplasty . 2012 Sep;27(8 Suppl):12-6 Disclosure of Interest: None Declared